2006
DOI: 10.1111/j.1538-7836.2006.02117.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma contains protein S monomers and multimers with similar direct anticoagulant activity

Abstract: Summary. Background: Protein S (PS) has activated protein C-independent, direct anticoagulant activity (PS-direct). We reported that both multimers and monomers of affinity-purified PS have PS-direct similar to that in plasma, in contrast to another report. Objective: We extended our studies to establish the molecular forms and activity of plasma PS. Methods: Novel ELISAs were developed that could detect only multimeric, not monomeric, PS because they employed the same monoclonal antibody for capture and detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…91 Similar high-molecularweight multimeres of protein S have been observed in plasma and reported to possess equal anticoagulant properties as the monomers. 92 Membranes that contain phosphatidylserine serve as a scaffold for the auto-oxidation of Cys residues in protein S, which promotes the oligomerization of protein S required for Mer-dependent apoptotic cell clearance. 73 This oligomerization may also provide a mechanism that allows the abundant protein S to activate Mer when necessary and not constitutively.…”
Section: Discussionmentioning
confidence: 99%
“…91 Similar high-molecularweight multimeres of protein S have been observed in plasma and reported to possess equal anticoagulant properties as the monomers. 92 Membranes that contain phosphatidylserine serve as a scaffold for the auto-oxidation of Cys residues in protein S, which promotes the oligomerization of protein S required for Mer-dependent apoptotic cell clearance. 73 This oligomerization may also provide a mechanism that allows the abundant protein S to activate Mer when necessary and not constitutively.…”
Section: Discussionmentioning
confidence: 99%
“…29 Whether multimers of PS are present in plasma or are generated during PS purification is controversial. [29][30][31][32][33] More recently, it was shown that PS enhances the inhibition of FXa by TFPI-␣ and that this action of PS is apparent with monomeric PS. 12,13,34 TFPI-␣ regulates blood coagulation by directly inhibiting FXa through its K2 domain and, in a FXa-dependent fashion, inhibiting FVIIa/TF through its K1 domain.…”
Section: Discussionmentioning
confidence: 99%
“…However, they observed that protein S multimers were not observed in plasma and so concluded that these forms of protein S are unlikely to contribute to protein S direct in plasma. Whether protein S multimers are present in plasma or generated during purification is also a matter of debate (27)(28)(29)(30). In our studies, we have used commercial protein S preparations that essentially have only protein S monomers.…”
Section: Discussionmentioning
confidence: 99%